2008
DOI: 10.1192/bjp.bp.107.044677
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality study of paranoid thinking in the general population

Abstract: This is the most unambiguous demonstration of paranoid ideation in the general public so far. Paranoia can be understood in terms of cognitive factors. The use of virtual reality should lead to rapid advances in the understanding of paranoia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
184
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(210 citation statements)
references
References 39 publications
14
184
1
1
Order By: Relevance
“…Our central findings, in a sample of relatively high-functioning college students, are loosely consistent with Freeman and colleagues's findings that the combination of anxiety and the experience of perceptual anomalies increases the risk that an individual will report feeling persecuted (Freeman et al, 2005a;Freeman et al, 2008a;Freeman et al, 2008b). However, the effects of anxiety and perceptual aberrations appear to be independent and additive, with each making distinct, if subtle, contributions to different aspects of paranoid thinking.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our central findings, in a sample of relatively high-functioning college students, are loosely consistent with Freeman and colleagues's findings that the combination of anxiety and the experience of perceptual anomalies increases the risk that an individual will report feeling persecuted (Freeman et al, 2005a;Freeman et al, 2008a;Freeman et al, 2008b). However, the effects of anxiety and perceptual aberrations appear to be independent and additive, with each making distinct, if subtle, contributions to different aspects of paranoid thinking.…”
Section: Discussionsupporting
confidence: 88%
“…Unlike prior research focused on anxiety, perceptual anomalies, and paranoia, which has typically treated paranoia as a unidimensional construct (e.g., (Freeman et al, 2005a;Freeman et al, 2005b;Freeman et al, 2008b;Martin et al, 2001), we examined associations among social anxiety, perceptual abnormalities, and Rawlings and Freeman's (1996) five proposed factors for sub-clinical paranoia, which they based on a factor analysis of a large item set drawn from established, theoretically-driven measures of paranoia and related constructs. We elected to use Rawlings and Freeman's (1996) model for two primary reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Negative emotions (anxiety and depression) have also been shown to be associated with dimensions of paranoia in clinical and non-clinical populations (Freeman et al 2005(Freeman et al , 2008, and there is strong evidence from large clinical cohort studies that they are specifically implicated in the development and maintenance of persecutory delusions Fowler et al 2012). Such affective dysregulation has been suggested to be an aetiological pathway to psychosis (van Os & Kapur, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In front of them they could see an audience composed of a small number of animated virtual characters. [14], the London underground [2], the Milgram recreation [16], the virtual bar [11], the socially anxious virtual character [12] and the medical consultation [13].…”
Section: Slater's Experiments On Virtual Charactersmentioning
confidence: 99%
“…Freeman et al [2] ran an experiment in which participants stood inside a virtual London underground train containing a number of virtual characters that were programmed to have neutral behavior and not interact with the participant. They found that participants with a history of paranoid delusions and also a sizable proportion of healthy members of the public had paranoid thoughts about the virtual characters thoughts and behavior towards them even though the characters behavior was objectively unrelated to the participant.…”
Section: Slater's Experiments On Virtual Charactersmentioning
confidence: 99%